Long‐term outcomes of radical prostatectomy versus low‐dose‐rate brachytherapy in patients with intermediate‐risk prostate cancer: Propensity score matched comparison. Issue 2 (29th September 2022) - Urabe, Fumihiko; Miki, Kenta; Kimura, Takahiro; Sasaki, Hiroshi; Tashiro, Kojiro; Iwatani, Kosuke; Matsukawa, Akihiro; Aikawa, Koichi; Tsusumi, Yuki; Morikawa, Midoriko; Minato, Kyosuke; Sato, Shun; et al.
Abstract: Purpose: To compare long‐term outcomes of radical prostatectomy (RP) and low‐dose‐rate brachytherapy (LDR‐BT) using propensity score‐matched analysis in patients with clinically localized, intermediate‐risk prostate cancer (PCa). Methods: Between October 2003 and March 2014, our institution treated 1241 patients with intermediate‐risk PCa (RP: n = 531; LDR‐BT: n = 710). Biochemical recurrence (BCR) was defined as prostate‐specific antigen (PSA) levels of 0.2 ng/ml or greater for RP, and as PSA nadir plus 2 ng/ml or higher (Phoenix definition) for LDR‐BT. We calculated propensity scores by multivariate logistic regression based on covariates that included age, pretreatment PSA, biopsy Gleason grade, the percentage of positive biopsy cores (PPBC), and clinical T stage. Results: Median follow‐up was 108 months for RP and 99 months for LDR‐BT. After propensity score adjustment, a total of 642 (321 each) patients remained for further analysis. Kaplan–Meier curves showed no statistically significant difference in overall survival (OS) ( p = 0.99). LDR‐BT was associated with improved BCR‐free survival and salvage therapy‐free survival compared to RP ( p < 0.001), and RP was associated with improved metastasis‐free survival (MFS, p < 0.001). Conclusion: BCR cannot be a surrogate for survival comparison, primarily due to differences between treatment modalities in how this term was defined post‐therapy. Long‐term follow‐up showed that RP was associated with lower MFS in intermediate‐risk PCa. However, this has not yet translated into superior OS.